2018
DOI: 10.1002/qua.25792
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the microhydration processes of iodine nitrogen oxides

Abstract: This work reports for the first time the structures and the thermodynamics of the microhydrates of iodine nitrogen oxides (INO x ). Monohydrates and dihydrates were investigated for five different INO x species (INO, INO 2 , cis-IONO, trans-IONO, and IONO 2 ). The structures of the water complexes were characterized at the ωB97XD/aug-cc-pVTZ level of theory. Coupled-cluster calculations were performed with the ANO-RCC-VQZP basis sets. Standard reaction enthalpy and standard Gibbs free reaction energy (Δ r G 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(48 reference statements)
4
5
0
Order By: Relevance
“…This difference is increasing when adding more water molecules to the aggregates. These variations are close to the ones noticed in the iodine nitroxides microhydration processes . When considering the most stable molecular complex in terms of standard Gibbs free energy at 298 K, we observed that the monohydration of HOIO is characterized by Δ r G ° 298K > 0 at the DK-CCSD­(T)-cf level, while the next hydration reactions ( n = 2, 3, 4) exhibit negative Gibbs free energies.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This difference is increasing when adding more water molecules to the aggregates. These variations are close to the ones noticed in the iodine nitroxides microhydration processes . When considering the most stable molecular complex in terms of standard Gibbs free energy at 298 K, we observed that the monohydration of HOIO is characterized by Δ r G ° 298K > 0 at the DK-CCSD­(T)-cf level, while the next hydration reactions ( n = 2, 3, 4) exhibit negative Gibbs free energies.…”
Section: Resultssupporting
confidence: 84%
“…Optimized geometry parameters and vibrational frequencies for H 2 O at the ωB97X-D/aug-cc-pVTZ level of theory have been already presented in our last studies. , The corresponding data for iodous acid are presented in Tables S1 and S2 of the Supporting Information. Comparison with the previous data obtained by Khanniche et al at the B3LYP/aug-cc-pVTZ level of theory shows slight differences between the bond lengths (<0.034 Å) and angles (<1°).…”
Section: Resultsmentioning
confidence: 99%
“…Optimized geometric parameters and vibrational frequencies for H 2 O at the ωB97X-D/aug-cc-pVTZ level have been already presented in previous studies. The BrHgO geometry was previously computed by Balabanov et al, at CCSD­(T)/CBS, and our geometry compares well with their results. For HOHg, our HgO bond length is also longer (by 0.038 Å) than that computed by Dibble et al, at the CCSD­(T,full)/AwCVTZ level.…”
Section: Discussionsupporting
confidence: 70%
“…At the RCCSD(T)/CBS, we compute BEs (in kcal mol −1 ) of −1.541 for OI–N 2 and −0.768 for IO–N 2 , of −1.260 for OI–CO and of −1.051 for IO–CO, of −2.079 for OI–CO 2 and −1.974 for IO–CO 2 , and of −4.991 for OI–H 2 O and −2.738 for IO–H 2 O. The presently found over stability of the halogen bonded complexes vs. the hydrogen bonded complexes was already noticed for IO–Ar, 28 for monohydrates of IO, 34,59 of ClO, 72 of BrO, 72 of INO, 73 and of INO 2 , 73 for hypoiodous acid interacting with CO ( i.e. HOI–CO) 74 and for hypoiodous acid interacting with NH 3 ( i.e.…”
Section: Resultsmentioning
confidence: 86%